The Indonesian and French Justice System (in Comparison of Structure and Mechanism) - Putri Cahyawati, Dwi; Burhanuddin, Nizam (KnE Social Sciences, 2024)
The Indonesian and French justice systems share similarities in structure, mechanism, and trial stages. However, the Indonesian system is considered better due to its structure and non-overlapping trial examination mechanisms. The highest court in Indonesia is the Supreme Court, while in France, the highest court is the Courts de Cassation and the Council of Cassation. Experts often reference the French judicial system, but the author believes the existing judiciary, particularly the Constitutional Court, should be maintained, and there is no need to imitate the French judicial system. Keywords: strict liability, criminal acts, environmental crime